2002
DOI: 10.1046/j.1524-4725.2002.02095.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal Treatment of Acne Scars With Trichloroacetic Acid: Chemical Reconstruction of Skin Scars Method

Abstract: CROSS is a safe and very effective single modality for the treatment of atrophic acne scars with no significant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(156 citation statements)
references
References 19 publications
4
144
0
3
Order By: Relevance
“…In order to maximize the effects of TCA and to overcome complications such as scarring, hyperpigmentation, and hypopigmentation, focal application of higher TCA concentrations on the pigmented areas only by using a sharpened wooden applicator. This method has the advantages of more rapid healing time and a lower complication [8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to maximize the effects of TCA and to overcome complications such as scarring, hyperpigmentation, and hypopigmentation, focal application of higher TCA concentrations on the pigmented areas only by using a sharpened wooden applicator. This method has the advantages of more rapid healing time and a lower complication [8].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical reconstruction of skin scars (CROSS) method is a technique consisting of the focal application of higher trichloroacetic acid (TCA) concentrations by pressing hard on the entire depressed area of atrophic acne scars using a sharpened wooden applicator [7]. Several studies showed the excellent effect of the CROSS method in the treatment of acne scars, and we have also used CROSS method for acne scars with good results [8].…”
Section: Introductionmentioning
confidence: 99%
“…This property was also reported by Fernandes et al 12 The percentage improvement in group "B" which underwent TCA CROSSS was 78%.The results are in concordance with the study done by Lee et al where they reported an improvement of 68% after 3 sessions of TCA. 13 The improvement in scars is cumulative with more sessions giving greater percentage improvement. In a study done by Yug et al the percentage improvement was 50.5% after 6 sessions at six weeks interval.…”
Section: Discussionmentioning
confidence: 99%